(untitled) - Channon, Derek F. (London, 1973)
This book introduce the changing nature of British enterprise. The British industrial environment. Diversification and divisionalization. The undiversified enterprises...
Keywords: Quản trị công nghiệp,Industrial management; Nước Anh,Great Britain